Promises and Limits of Web-deliberation - Kies, R. author. aut Link
XII, 188 p.
Keywords: Does the increasing usage of online political forums lead to a more deliberative democracy? This book presents the evolution of the public spaces in a historical perspective, by defining and operationalizing the deliberative criteria of democracy, and by measuring and evaluating the impact of virtualization of the political debates.